Corrosion Behavior of Common Metals in Eutectic Ionic Liquids - Ibrahim, Taleb (2019)
The corrosion behavior of six choline chloride-based eutectic solvents namely, ChCl-Ur, ChCl-EG, ChCl-Gl, ChCl-MA, ChCl-Ph and ChCl-TG towards copper, mild steel and stainless steel 316 have been investigated. The effect of temperature and moisture content was evaluated. The corrosion rates of the three materials increased with an increase in the temperature and moisture content. Stainless steel was found to be the most resistant under all experimental conditions. The experimental results demonstrated ChCl-Ph and ChCl-Gl to have high inhibition efficiency suggesting these to be a suitable candidate as green corrosion inhibitors for metal and alloys under extreme environments.